Penerapan Media Pembelajaran Crossword Puzzle pada Mata Pelajaran Fiqih Kelas XII di MAN 1 Kota Bukittinggi - Sari, Indah Nirmala; Junaidi, Junaidi (Lembaga Yasin AlSys, 2025)
Good learning begins with educators' accuracy in choosing learning media. Learning media aims to motivate students to participate in the learning process. One of the efforts made by the class XII fiqh teacher was choosing the Crossword Puzzle learning media for its application in the classroom. In this learning media, the teacher makes small boxes and creates questions on the sheet, which later in these boxes the answers to the questions are entered. This learning media aims to increase students' motivation in the learning process, because this learning media contains game elements, which makes students motivated. This research uses a qualitative type of field research. The data collection technique is by conducting interviews, observation, documentation. The technique for analyzing the data uses descriptive analytical techniques with a qualitative approach. Based on the results of the research carried out, it can be stated that the application of the Crossword Puzzle learning media in class And there are also several obstacles when implementing this Crossword Puzzle learning media, namely that there are still many students who consider this learning media as just a toy.